Drosophila Vps4 promotes Epidermal growth factor receptor signaling independently of its role in receptor degradation - Legent, Kevin (Development, 2015)
Endocytic trafficking of signaling receptors is an important mechanism for limiting signal duration. Components of the Endosomal Sorting Complexes Required for Transport (ESCRT), which target ubiquitylated receptors to intra-lumenal vesicles (ILVs) of multivesicular bodies, are thought to terminate signaling by the epidermal growth factor receptor (EGFR) and direct it for lysosomal degradation. In a genetic screen for mutations that affect Drosophila eye development, we identified an allele of Vacuolar protein sorting 4 (Vps4), which encodes an AAA ATPase that interacts with the ESCRT-III complex to drive the final step of ILV formation. Photoreceptors are largely absent from Vps4 mutant clones in the eye disc, and even when cell death is genetically prevented, the mutant R8 photoreceptors that develop fail to recruit surrounding cells to differentiate as R1-R7 photoreceptors. This recruitment requires EGFR signaling, suggesting that loss of Vps4 disrupts the EGFR pathway. In imaginal disc cells mutant for Vps4, EGFR and other receptors accumulate in endosomes and EGFR target genes are not expressed; epistasis experiments place the function of Vps4 at the level of the receptor. Surprisingly, Vps4 is required for EGFR signaling even in the absence of Shibire, the Dynamin that internalizes EGFR from the plasma membrane. In ovarian follicle cells, in contrast, Vps4 does not affect EGFR signaling, although it is still essential for receptor degradation. Taken together, these findings indicate that Vps4 can promote EGFR activity through an endocytosis-independent mechanism.